Հնագիտական նորահայտ առարկաներ հին Արտաշատից - Հովհաննես Օհանյան (Մայր Աթոռոյ Սրբոյ Էջմիածնի)
Представленный археологический материал был обнаружен на территории древнего Арташата не в следствии систематических раскопок, проводимых научными методами, а путем разграбления и уничтожения памятников кладоискателями. Цель данного отчета – сделать возможным использование данного материала в научных кругах и как-то восполнить некоторый пробел в изучении материальной культуры Арташата – древней столицы античной Армении. The presented archaeological material was discovered on the territory of old Artashat not as a result of systematic excavations conducted by scientifi c methods, but as a result of looting and destruction of monuments by treasure hunters. The purpose of this report is to make it possible to use this material in scientifi c circles and somehow fi ll a certain gap in the study of the material culture of Artashat, the old capital of ancient Armenia.
Keywords: Auxiliary Sciences of History; Numismatics; Archaeology